Ekspresi Estetika dan Spiritualitas Sedekah Gunung Khas Padepokan Tjipta Boedaja Berbasis Teosentrisme - Gempur Sentosa; Sunarmi Sunarmi; Sarwanto Sarwanto (PANGGUNG, 2026)
Slametan and spirituality through art serve as a means of communicating with God and the universe amid an unbalanced natural environment. This study discusses aesthetic expression and spirituality through a theocentric perspective in the Sedekah Gunung activity at Padepokan Tjipta Boedaja Tutup Ngisor, Magelang. This study uses qualitative methods with a fieldwork approach, including interviews, field observations, transcription, data processing, and systematic data compilation. The results show that the aesthetic and spiritual expressions of Sedekah Gunung are embedded in a theocentric perspective in the meditasi gerak solah bawa and the kidung tradisi Sedekah Gunung. Theoretically, this research contributes to the development of a research model for aesthetic and spiritual expression in music and dance, grounded in theocentrism as a perspective. In practice, this research contributes to the discovery and explanation of aesthetic meaning through the kidung tradisi sedekah gunung and meditasi gerak (solah bawa).